If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -1) + -17(x + -3) = 4(4x + -9) + 4 Reorder the terms: 8(-1 + x) + -17(x + -3) = 4(4x + -9) + 4 (-1 * 8 + x * 8) + -17(x + -3) = 4(4x + -9) + 4 (-8 + 8x) + -17(x + -3) = 4(4x + -9) + 4 Reorder the terms: -8 + 8x + -17(-3 + x) = 4(4x + -9) + 4 -8 + 8x + (-3 * -17 + x * -17) = 4(4x + -9) + 4 -8 + 8x + (51 + -17x) = 4(4x + -9) + 4 Reorder the terms: -8 + 51 + 8x + -17x = 4(4x + -9) + 4 Combine like terms: -8 + 51 = 43 43 + 8x + -17x = 4(4x + -9) + 4 Combine like terms: 8x + -17x = -9x 43 + -9x = 4(4x + -9) + 4 Reorder the terms: 43 + -9x = 4(-9 + 4x) + 4 43 + -9x = (-9 * 4 + 4x * 4) + 4 43 + -9x = (-36 + 16x) + 4 Reorder the terms: 43 + -9x = -36 + 4 + 16x Combine like terms: -36 + 4 = -32 43 + -9x = -32 + 16x Solving 43 + -9x = -32 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 43 + -9x + -16x = -32 + 16x + -16x Combine like terms: -9x + -16x = -25x 43 + -25x = -32 + 16x + -16x Combine like terms: 16x + -16x = 0 43 + -25x = -32 + 0 43 + -25x = -32 Add '-43' to each side of the equation. 43 + -43 + -25x = -32 + -43 Combine like terms: 43 + -43 = 0 0 + -25x = -32 + -43 -25x = -32 + -43 Combine like terms: -32 + -43 = -75 -25x = -75 Divide each side by '-25'. x = 3 Simplifying x = 3
| -4x+2=8x+1 | | X+.05x=71000000 | | (5x+3)(-x+4)= | | 10a^2+84a+98=0 | | 7x-2=-14 | | -27+4g=33 | | 15x^2+123x-108=0 | | 18m=6m | | 2x^3-17x=0 | | 3-2x=x^2+3x-3 | | 4x+5=2x-8 | | 5k^3-26k^2+24k=0 | | 2x^3-17=0 | | x+(x-1)=55 | | 74=4+2b | | ln(3x+6)=7 | | 3(4x-1)=6 | | 6y=3x+2 | | 30x-(-x+6)+(-5x+4)=-(5x+6)+(-8+30) | | X^2+4x-y-6=0 | | (2cos^2x-1)-cosx=0 | | 24b=6b | | 20*8= | | X+6(x+2)=3x-4 | | -8x+(-5x)=x | | (3k+2)(3k+2)=49 | | x^2+25x-4344=0 | | 2x^3y^3+3x^2y^2+4y=0 | | 10+4(-3)=x | | (7x-11)(3x-8)=0 | | 2/3+a-5/9=-a+2a | | X^2+y^2-10x-4y+20=0 |